An Almost Old Gravitational Theory Solves the Crisis of Physics - Petry, Walter (European Journal of Applied Sciences, 2024)
It is well-known that there is a crisis of physics which is stated by several authors. The author of this article has already given a new theory of gravitation in the year 1979 several years ago and totally different from General Relativity (GR). It is a field theory and not geometry. The redshift of galactic objects e.g. galaxies is by the use of this theory a gravitational effect and not a Doppler one as stated by Hubble and as accepted by almost all scientists today. Einstein has already remarked by the use of GR implying that redshift may also be a gravitational effect as also given by the new theory of gravitation and not a Doppler one. This is the reason for the crisis of physics as noted by many scientists. All of my submitted articles use this new theory of gravitation which I published in the death year 1979 of the great physicist Albert Einstein.